Pembuatan Konten Tiktok dan Kerangjang Kuning Untuk Ekonomi Kreatif TSB Lure di Desa Bangka Kotra Kabupaten Bangka Selatan - Cik Marhayani; Rita Deseria; Suratmi Suratmi; Parhastama Parhastama; Serli Marcelina; Dwihana Prajawati; Aprillian Aprillian; Dwi Ariyanti; Sherly Sulvi Restia; Desmita Pramesti; Kharisma Kharisma (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Limited digital literacy remains a challenge for micro, small, and medium enterprises (MSMEs) in utilizing social media as a marketing tool. MSMEs TSB LURE in Bangka Kota Village, South Bangka Regency, face problems in expanding their market reach because their marketing strategies are still conventional. This community service activity aims to improve the digital marketing capacity of MSMEs through the use of the TikTok platform. The method used is Participatory Action Research (PAR), which actively involves partners in every stage of the activity, from problem identification, digital literacy training, content production assistance, to the implementation of TikTok Shop with the yellow basket feature. The results of the activity showed significant improvements, namely an increase in followers from 15 to 245, an increase in promotional content from 0 to 12, audience interaction reaching more than 350, and 65 clicks on the yellow basket. These achievements not only increased product visibility but also fostered social change in the form of the emergence of creative youth groups, local leaders from SME actors, and new awareness about the use of digital technology in supporting the local creative economy.